Trinitarian ontology and Israel in Robert W. Jenson's theology - Lee, Sang-hoon (Eugene, OR : Pickwick Publications, 2016)
"Can Christian theology overcome its long-standing supersessionism without diluting its trinitarian faith? Can Christian faith remain genuinely Christian when it fails to recognize the covenantal significance of the Jews? In his later career, a leading trinitarian theologian Robert Jenson's theology moves in a post-supersessionistic direction. That said, the conceptual nexus between his trinitarian theology and his post-supersessionism is not always patent on the surface of his texts. In this book, Lee traces the post-supersessionistic development of Jenson's trinitarian theology and uncovers the reasons why Jenson's trinitarian theology sets out to embrace the existence of the Jews. This book seeks to show that Jenson's revisionary-historicized, "carnalized", hermeneutical, and eschatological-trinitarian ontology allows for genuine confession of the eternal triune God as the God of Israel, and that it thereby lays a firm basis for a properly Christian post-supersessionism."
Includes bibliographical references and index.
Description based on print version record.
Master record variable field(s) change: 072, 082
Keywords: Jenson, Robert W; Trinity; Christianity and other religions -- Judaism; Theology; RELIGION / Christian Theology / General; Electronic books